Adjusting an institutional framework to a globalising world: the creation of new institutions in the EEC, 1957-1992. Issue 3 (2nd July 2020) - Mourlon-Druol, Emmanuel
ABSTRACT: This article explores the development of all new EEC institutions between 1957 and 1992 within policy areas relevant to the possible development of a European single currency. It argues that if most institutions created pre-1992 were not crisis management institutions as would be the case post-2008, some important institutions were created in response to the perception of a structural international banking/political/economic crisis, particularly in the 1970s. This comparison in time underlines the continuity of reflections about the missing elements of a functioning single currency area, the obstacles to reform, and sheds light on the radical institutional changes that occurred post-2008.